An Examination of Customary and Statutory Legal Meaning of a Child in Nigeria: a Stream of Two Water that does not Mix - Akpa Michael Ajanwachuku (Universitas Lampung, 2017)
The Nigerian legal system is pluralistically consisting of statutory law, which is derived from received English law and native customary law. The latter is made subservient to the former through the validity tests. This paper examined the position of the two regimes on the meaning and definition of the child and the legal consequences that arise from it. The paper found that while the two legal regimes conceptualize the ‘child’ differently, there is an acute internal divergence of who a child is, within each of these regimes. The paper recommended both the internal and inter-systemic harmonization of the meaning and definition of the child within the Nigerian legal system. Keywords: Nigerian Child, Customary Law, Statutory Law, Validity Tests, Child’s Rights Act